Role of Calcium and Alkaline Phosphatase in Bone growth and its impact on Osteoporosis - Uppin, Anju B.; Tubaki, B. R.; Patil, Kiran (Journal of Neonatal Surgery, 2025)
Aim: The objective of this study is to determine bone mineral density (BMD) and the biochemical markers with variation in healthy, osteopenic and osteoporotic individuals. It reviews the part of alkaline phosphatase in assessment of bone metabolism and osteoporosis progression. The research also looks into the interaction of the calcium levels and estrogen deficiency in relation to bone health. Methods: A total of three groups (healthy individuals, osteopenia and osteoporosis) were studied in a cross-sectional manner. Dual energy X-ray absorptiometry (DEXA) was used to measure BMD; and also, the serum samples analyzed for biochemical markers of calcium levels. The statistical comparison to identify the significant within the groups and correlation between biomarkers and the severity of osteoporosis were performed. Results: Osteopenic and osteoporotic individuals’ BMD is significantly lower than that in healthy group. With ALP levels higher also, osteoporotic participants showed increased bone turnover. There was only minor variation of calcium level except osteopenic and osteoporotic individuals showed a significant difference. The research further proves that estrogen deficiency greatly contributes to bone loss and the risk of fractures. Conclusion: The finding of this study supports the importance of early detection and treatment of osteoporosis. BMD and biochemical markers simultaneously are used in combination for diagnosing (and monitoring) of bone health. Calcium supplementation, probiotics, as well as targeted molecular therapies based on a molecular analysis of luminal HC p5S fractions are recommended. With the success of chondroprotective nanotechnology, more work on novel interventions nanotechnology-based supplements and gene targeted treatments for osteoporosis prevention and treatment outcomes needs to happen.